OP0185 Emergency department visits for gout: a dramatic increase in the past decade. (12th June 2018) - Mithal, A.; Singh, G.
Abstract : Background: Several studies have suggested that the prevalence of gout has been increasing worldwide, perhaps related to lifestyle factors. 1–2 In the US, the NHANES study found a significantly higher age-adjusted prevalence (3.9%) in 2007–2008 than the estimate in 1988–1994 (2.9%). This trend paralleled an observed increase in hyperuricemia. 1 Objectives: To study emergency department visits due to gout in the US over 9 years (2006 to 2014). Methods: The Nationwide Emergency Department Sample (NEDS) is the largest all-payer emergency department (ED) database in the United States, yielding national estimates of hospital-based ED visits. It contains information from 31 million ED visits at 945 hospitals in 34 states that approximate a 20-percent stratified sample of U.S. hospital-owned EDs. Weighted, it estimates roughly 143 million ED visits. We studied all ED with primary diagnosis of Gout (ICD9 code 274.xx) from 2006–2014 and calculated prevalence in different age groups. Population data was obtained from US census bureau. Results: Over last 9 years, 1.7 million people visited EDs with a primary diagnosis of acute gout. The total number of ED visits per year increased from 1 68 580 in 2006 to 2 13 780 in 2014, an increase of 26.8%. The prevalence of emergency room visits with primary diagnosis of gout increased from 56.5/100, 000 population in 2006 to 67/100, 000 in 2014 (p<0.001). The largest increase in ED visits was a 28% increase in prevalence among the 45–64 years age group from 91/100, 000 to 116/100, 000 (27%, p<0.001). Men were responsible for 78% of the ED visits in both 2006 and 2014. Conclusions: Emergency Department visits have increased dramatically in the US over the last 9 years, and this increase is mostly in the 45–64 years age group perhaps reflecting the undermanaged burden of uncontrolled gout. Education, improved recognition and long-term management as well as increased use of preventive strategies is needed. References: [1] Lawrence RC, et al. Estimates of the prevalence of arthritis and other rheumatic conditions in the United States. Part II. Arthritis Rheum2008;58(1):26–35. [2] Kuo CF, et al. Global epidemiology of gout: Prevalence, incidence and risk factors. Nat Rev Rheumatol2015;11(11):649–62. Disclosure of Interest: A. Mithal: None declared, G. Singh Grant/research support from: Horizon Pharma